1984
DOI: 10.1121/1.391401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the temporal pattern of a given noise dose on TTS in guinea pigs

Abstract: To show the effect of the temporal pattern of acoustic stimulation on TTS 15 min, guinea pigs were subjected to isoenergetic noises with the same spectrum. The exposures in a first experimental series were continuous noises and noise bursts. The continuous noise was presented with different durations and levels but always with the same energy. The noise burst stimulation consisted of a constant number of bursts with different interstimulus intervals. Both duration and repetition rate were shown to affect the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These could include noise-induced hearing loss and auditory system damage, temporary hearing loss (called temporary threshold shift [TTS]), and masking of communication and other important biological sounds (e.g . Miller 1974;Buck et al 1984;Clark 1991;Adler et al 1992;Ryals et al 1999;Le Prell et al 2012). Increased noise can also cause behavioral and/or physiological changes, such as increased stress, sleep loss and hormonal changes (Miller 1974;Brumm 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These could include noise-induced hearing loss and auditory system damage, temporary hearing loss (called temporary threshold shift [TTS]), and masking of communication and other important biological sounds (e.g . Miller 1974;Buck et al 1984;Clark 1991;Adler et al 1992;Ryals et al 1999;Le Prell et al 2012). Increased noise can also cause behavioral and/or physiological changes, such as increased stress, sleep loss and hormonal changes (Miller 1974;Brumm 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although relatively little is known about the effects of manmade sounds on fishes, a good deal may be inferred about the potential effects, and approaches to the study of those effects, from the wealth of data available from humans and laboratory animals (Miller ; Buck et al ; Clark ; Passchier‐Vermeer & Passchier ; Le Prell et al ). For example, we surmise that a similar range of adverse effects found in humans and other mammals occurs in birds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The factors associated with TS-like sound level (i.e., sensation level, overall level, and level above background), the duration, duty cycle (intermittent or continuous), number of transient components, and frequency of sound are all important considerations (e.g., Buck et al 1984;Clark et al 1987;Ward 1991;Lataye and Campo 1996). This is especially the case for exposure to impulsive sound sources (Danielson et al 1991;Henderson et al 1991;Hamernik et al 2003), which is why acoustic thresholds in this technical guidance are also expressed as a Peak SPL Metric (PK).…”
Section: Technical Guidelines For Marine Mammalsmentioning
confidence: 99%
“…This paper presents the results of an experiment designed to determine what, if any, difference exists between the trauma produced by impulsive and Gaussian noise exposures at moderate levels. The basic idea, which was similar to the Buck et al (1984) approach, was to use three noise exposures, each having the same SEL and spectra, but differing in their phase spectrum so that the time waveform could be varied from a Gaussian noise to a pure impact noise exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Buck et al (1984) exposed guinea pigs to impulsive or continuous noise at equivalent energies. Using the round window AP to obtain threshold shift (TS) measures, they showed that impulsive stimulation produced up to 25 dB greater TS for the same SEL and that the maximum effect was found one-half octave higher than that produced by continuous stimulation.…”
Section: Introductionmentioning
confidence: 99%